Validation of GWAS-Identified Variants for Anti-TNF Drug Response in Rheumatoid Arthritis: A Meta-Analysis of Two Large Cohorts - Sánchez-Maldonado, Jose Manuel; Cáliz, Rafael; López-Nevot, Miguel Ángel; Cabrera-Serrano, Antonio José; Moñiz-Díez, Ana; Canhão, Helena; Ter Horst, Rob; Quartuccio, Luca; Sorensen, Signe B.; Glintborg, Bente; Hetland, Merete L.; Filipescu, Ileana; et al. (Frontiers in Immunology, 2021)
We aimed to validate the association of 28 GWAS-identified genetic variants for response to TNF inhibitors (TNFi) in a discovery cohort of 1361 rheumatoid arthritis (RA) patients monitored in routine care and ascertained through the REPAIR consortium and DANBIO registry. We genotyped selected markers and evaluated their association with response to TNFi after 6 months of treatment according to the change in disease activity score 28 (DAS28). Next, we confirmed the most interesting results through meta-analysis of our data with those from the DREAM cohort that included 706 RA patients treated with TNFi. The meta-analysis of the discovery cohort and DREAM registry including 2067 RA patients revealed an overall association of the LINC02549rs7767069 SNP with a lower improvement in DAS28 that remained significant after correction for multiple testing (per-allele ORMeta=0.83, PMeta=0.000077; PHet=0.61). In addition, we found that each copy of the LRRC55rs717117G allele was significantly associated with lower improvement in DAS28 in rheumatoid factor (RF)-positive patients (per-allele ORMeta=0.67, P=0.00058; PHet=0.06) whereas an opposite but not significant effect was detected in RF-negative subjects (per-allele ORMeta=1.38, P=0.10; PHet=0.45; PInteraction=0.00028). Interestingly, although the identified associations did not survive multiple testing correction, the meta-analysis also showed overall and RF-specific associations for the MAFBrs6071980 and CNTN5rs1813443 SNPs with decreased changes in DAS28 (per-allele ORMeta_rs6071980=0.85, P=0.0059; PHet=0.63 and ORMeta_rs1813443_RF+=0.81, P=0.0059; PHet=0.69 and ORMeta_rs1813443_RF-=1.00, P=0.99; PHet=0.12; PInteraction=0.032). Mechanistically, we found that subjects carrying the LINC02549rs7767069T allele had significantly increased numbers of CD45RO+CD45RA+ T cells (P=0.000025) whereas carriers of the LINC02549rs7767069T/T genotype showed significantly increased levels of soluble scavengers CD5 and CD6 in serum (P=0.00037 and P=0.00041). In addition, carriers of the LRRC55rs717117G allele showed decreased production of IL6 after stimulation of PBMCs with B burgdorferi and E coli bacteria (P=0.00046 and P=0.00044), which suggested a reduced IL6-mediated anti-inflammatory effect of this marker to worsen the response to TNFi. In conclusion, this study confirmed the influence of the LINC02549 and LRRC55 loci to determine the response to TNFi in RA patients and suggested a weak effect of the MAFB and CNTN5 loci that need to be further investigated.